Democracy, Human Capital, and the Neoliberal Arts - Brooks, Ryan; Mueller, Laura (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
It is no secret that humanities professors find themselves disenchanted by the current state of neoliberal universities; as the story goes, jobs are scarce, enrollment continues to drop, and students seem increasingly disconnected from the value of humanities-based classes. Universities and departments strive for new ways to respond to the current “crisis” in higher education internally, by appealing to the usefulness of the liberal arts, and structurally by institutionalizing the diversity of universities via DEI (diversity, equity, and inclusion) requirements and offices. On the surface, such measures seem “Deweyan” in spirit, by increasing social diversity, by removing class barriers, and by removing “waste” in the divisions between vocational and humanities studies. However, such responses to neoliberal institutions reproduce the very logic to which they respond and reflect a refusal to think institutionally. Using Dewey’s theories of democracy, growth, and waste, as well as contemporary literatures on the neoliberal university and virtue hoarding in education, we argue that these seemingly Deweyan measures reproduce the problems which they purport to resolve.